Determinan Ukuran Entitas, Profitabilitas, Dan Solvabilitas Terhadap Audit Delay - Moh. Abdulah Al Faris; Syaiful Bahri (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to determine and analyze the effect of firm size, profitability, and solvency on audit delay. Audit delay is the time span between the closing date of the financial year, which is December 31, until the date the audit opinion is issued in the audit report. The research population is mining entities listed on the Indonesia Stock Exchange for the 2019-2021 period. The non-probability sampling technique used purposive sampling method with a total of 20 entities. The data analysis technique used is multiple regression analysis. The results show that the size of the company has a significant effect on audit delay, meaning that the larger the size of the company as measured by the total assets or wealth owned by an entity, the time for completing the audit report will be completed. Profitability and solvency have no effect on audit delay.